ANALISIS PENGARUH PERSEPSI KEMUDAHAN, KEMANFAATAN,DANKEPERCAYAAN TERHADAP KEPUASANPENGGUNA LPSE: THE ANALYSIS OF EASE, USEFULNESS PERCEPTION AND TRUST ON LPSE USER - Johannes Johannes; Widdy Frima (DIGEST MARKETING, 2018)
This research purpose is to identify and analyze the perception of ease, usefulness and trust on LPSE’suser satisfaction. Sample size consists of 62 firms which have been registered and verified from the year of 2013 until June 2015 in LPSE Jambi city. To analysis data, descriptive analysis and multiple linear regression are used complemently. Based on research results it is found that partially and simultaneously, ease and use-fulness perception and trust have significant effect on user satisfaction. Further re-search that related to this topic is the effect of LPSE performance on good governance at the local government. Keywords : LPSE, perceived ease, perceived usefulness, trust, satisfaction.